Resources Research Based on Documents of Web of Science(WOS) on the Basis of Incite Platform - Jiajiang , (Advances in Social Sciences Research Journal, 2022)
A case study of shanghai ocean university based on documents of web of science(WOS),mainly gets data from incite platform.Research including author, journal citing and cited and journal from major. The time period from 2006 to present.This paper also discuss the potential issue during the utility of resources.